New methodology for a faster synthesis of SrSnO3 by the modified Pechini method - Lucena, G. L.; Souza, J. J N; Maia, A. S.; Soledade, L. E B; Longo, Elson [UNESP]; Souza, A. G.; Santos, I. M G (FapUNIFESP (SciELO), 2013)
SrSnO3, a perovskite-type complex oxide, was synthesized by the modified Pechini method using two different precursors, tin chloride and metallic tin. The first one is already traditional in the literature and it claims about 30 days, only for the cleaning of tin citrate aiming at the elimination of the chloride. The second route was developed by our research group and saves time, taking 6 h to complete the synthesis of the resin. The results show that SrSnO3 obtained from the metallic tin show a higher short range order, leading to a band gap value higher than those reported in the literature, besides a meaningful reduction in the formation of SrCO 3, as compared to the one obtained from tin chloride.
Keywords: Chemical synthesis; Perovskite; Stannate